The role of strain and polar discontinuity in magnetism in LaMnO3/SrTiO3/LaAlO3 heterostructures - Wu, Liang (2020)
Creating novel interfacial effects in quantum-matter-based heterostructures is at the heart of condensed matter physics and materials science. [1] Utilizing the subtle interplay among charge, spin, orbit and lattice degrees of freedom, these interfacial effects can act as additional knobs to control the future oxide electronics. Among these interplays, two particularly interesting effects, the inevitable strain effect induced by unequal lattice constants and the ubiquitous charge redistribution effect at interfaces with a polar discontinuity. .